2008
DOI: 10.3340/jkns.2008.44.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Tuberculoma Involving the Brain and Spinal Cord in a Patient with Miliary Pulmonary Tuberculosis

Abstract: J Korean Neurosurg Soc 44 : [36][37][38][39] 2008 Although tuberculosis of the central nervous system is well known, the incidence of intramedullary tuberculomas is low and a combination of intramedullary with intracranial tuberculomas is extremely rare. We report a case of disseminated tuberculoma involving brain and spine with miliary pulmonary tuberculosis in a 66-year-old woman initially presenting with fever, general weakness, back pain and motor weakness of both lower extremities. Despite medical ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 20 publications
0
19
0
2
Order By: Relevance
“…Imaging modality like CT and MRI scan revolutionized the diagnostic compatibility and exclusion of invasive procedures. As the evolving nature of granuloma showed as low intensity lesions with or without central hyper-intensity on T2 and hypo to iso-intense on T1 weighted images, besides one study showed iso-intense or hypo-intense core with hyper-intense rim on T2 and fluid-attenuated inversion recovery (FLAIR) images as a common presentation but in this study with the most presentation of multiple lesions associated with noncontrast visibility which was ultimately enhanced by the contrast, showed central hyper-intensity on T2 (55%) with meningeal enhancement (80%), FLAIR signals (35%) and hypo-intense core with hyper-intense rim (30%) reflecting the most of cases with early non caseating nature of tuberculoma 7,12,16,19 .…”
Section: Discussionmentioning
confidence: 66%
“…Imaging modality like CT and MRI scan revolutionized the diagnostic compatibility and exclusion of invasive procedures. As the evolving nature of granuloma showed as low intensity lesions with or without central hyper-intensity on T2 and hypo to iso-intense on T1 weighted images, besides one study showed iso-intense or hypo-intense core with hyper-intense rim on T2 and fluid-attenuated inversion recovery (FLAIR) images as a common presentation but in this study with the most presentation of multiple lesions associated with noncontrast visibility which was ultimately enhanced by the contrast, showed central hyper-intensity on T2 (55%) with meningeal enhancement (80%), FLAIR signals (35%) and hypo-intense core with hyper-intense rim (30%) reflecting the most of cases with early non caseating nature of tuberculoma 7,12,16,19 .…”
Section: Discussionmentioning
confidence: 66%
“…It is classified into pulmonary and extrapulmonary. In this patient, disseminated TB as part of extra-pulmonary TB resulted in tuberculoma of the brain2 in the central nervous system. Tuberculoma of the brain was documented rarely with HIV infection (<1% of extra-pulmonary TB infections with AIDS) 3 4.…”
Section: Discussionmentioning
confidence: 85%
“…Because the patient came with lower limb paralysis and bowel and bladder incontinence, prophylactically screening of the whole spine with sagittal screening of the brain was done. Park and Song 6 have recommended prophylactic cranial imaging in patients with intramedullary spinal cord tuberculoma, so that intracranial tuberculomas can be ruled out. Thacker and Puri 2 reported a case of a young girl who presented with progressive paraparesis, and imaging revealed intramedullary tuberculoma with incidental finding of multiple intracranial tuberculomas.…”
Section: Discussionmentioning
confidence: 99%